Value-focused thinking and interpretive structural modeling in the development of resilience-enhancing initiatives in SMEs - Gonçalves, J.; Ferreira, F.; Milici, A.; Ferreira, N. (Strategic Change, 2026)
Following the aftermath of the COVID-19 pandemic, small and medium-sized enterprises (SMEs) have faced growing challenges that underscore the critical need for enhanced organizational resilience. This study aims to bridge the gap in resilience research by offering a structured and practical decision-support tool to enhance the resilience of SMEs. Adopting a multiple-criteria decision analysis (MCDA) approach, combining value-focused thinking (VFT), and interpretative structural modeling (ISM), the study identifies and prioritizes key initiatives and factors affecting SME resilience. Specifically, using a constructivist, process-oriented methodology, we engaged an expert panel from diverse sectors, including technology, manufacturing, and services, to collaboratively develop a group cognitive map and an interpretive model that guide resilience-building efforts. The findings highlight a hierarchy of resilience determinants, offering actionable insights for SME managers to structure and implement targeted resilience-enhancing strategies. The originality of this study lies in its dynamic decision-support approach, tailored specifically for SMEs, which is particularly relevant in today's volatile, post-pandemic business environment. The results provide a significant contribution to the field by addressing critical gaps in SME resilience research and offering practical tools for organizational planning.